Advances in Brain Inspired Cognitive Systems 5th International Conference, BICS 2012, Shenyang, China, July 11-14, 2012. Proceedings - Zhang, Huaguang; Hussain, Amir.; Liu, Derong; Wang, Zhanshan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 5th International Conference on Brain Inspired Cognitive Systems, BICS 2012, held in Shenyang, Liaoning, China in July 2012. The 46 high-quality papers presented were carefully reviewed and selected from 116 submissions. The papers are organized in topical sections on biologically inspired systems, cognitive neuroscience, models of consciousness, and neural computation.
Keywords: Computer science; Database management; Information storage and retrieval systems; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Database Management; Information Storage and Retrieval; Pattern Recognition; Computation by Abstract Devices